Surgical team workload comparison for 4-port and single-port laparoscopic cholecystectomy procedures. (July 2019) - Lowndes, Bethany R.; Abdelrahman, Amro M.; Thiels, Cornelius A.; Mohamed, Amani O.; McConico, Andrea L.; Bingener, Juliane; Hallbeck, M. Susan
Abstract: Advanced minimally invasive procedures may cause postural constraints and increased workload and stress for providers. This study compared workload and stress across surgical team roles for 48 laparoscopic cholecystectomies (4-port vs single-port) using a task load index (NASA-TLX), a procedural difficulty question, and salivary stress hormones. Statistical analyses were performed based on the presence intra-cluster correlation within team roles, at α=0.05. The single-port technique resulted in an 89% increase in physical workload for the surgeon and 63% increase for the assistant (both p<0.05). The surgeon had significantly higher salivary stress hormones during single-port surgeries. The degree of procedural difficulty was positively correlated between the surgeon and most roles: resident (r=0.67), assistant (r=0.81), and technician (r=0.81). There was a statistically significant positive correlation between the surgeon and assistant for all selfreported workload measures (p<0.05). The single-port technique requires further improvement to balance surgical team workload for optimal patient safety and satisfaction. Highlights: Workload was compared for single-port and 4-port laparoscopic cholecystectomy. The surgical team generally agreed upon procedural difficulty. Single-port increased physical workload for the surgeon and assistant. The surgeon and assistant experienced higher workload than other team roles. There is a need for more balanced workload across surgical team roles.